INVESTIGATING STUDENTS RESPONSE OF USING VIDEO BASED LEARNING METHOD THROUGH YOUTUBE ON ENGLISH VOCABULARY LEARNING - Raihan Bhusaery; Andrie Chaerul; Acep Bahrum Kamil (INFOTECH journal, 2024)
The objective of this study is to investigate how vocabulary-learning students respond to video based learning as a method at SMPN 2 Ciampel. This research used qualitative methodolgy as the research design. Vocabulary is an important aspect of language development. But Students has problems in remembering vocabulary. The first thing that we have to do is by create new innovation to students in learning more about vocabulary of English language. That is by use the YouTube video for learning vocabulary. The data were collected using observation when the students watch the video from YouTube and interview the students. Based on the study's findings, students can benefit from watching vocabulary-learning videos on YouTube to increase their vocabulary proficiency. It also found that when students speak English, they become more active, brave, and motivated.